2006
DOI: 10.1051/forest:2006075
|View full text |Cite
|
Sign up to set email alerts
|

Variability of cutting regimes in small private woodlots of south-western France

Abstract: -The small scale forest holdings are very common in Europe, but their management is not well known. The classical principes of forest management and of silviculture being rarely applied, their management is often seen as purely opportunistic, and even chaotic. To overcome this first sight, a detailed analysis of management practices in six private woodlots from two municipalities in south western France was done, with semi-directive interviews of the owners and an dynamic analysis of a chronological series of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 19 publications
1
13
1
3
Order By: Relevance
“…De Blois et al (2001) hypothesized that the absence of relationship for the tree layer was linked to the past disturbances and that trees had a lower response rate to edge effect, leading more to changes in density than in composition for this forest layer (Murcia 1995). In our forest fragments, forest edges are more frequently logged than forest interiors (De Warnaffe et al 2006). This may explain the discrepancies between our results and those of de Blois et al (2001).…”
Section: Spatial Variablescontrasting
confidence: 60%
See 3 more Smart Citations
“…De Blois et al (2001) hypothesized that the absence of relationship for the tree layer was linked to the past disturbances and that trees had a lower response rate to edge effect, leading more to changes in density than in composition for this forest layer (Murcia 1995). In our forest fragments, forest edges are more frequently logged than forest interiors (De Warnaffe et al 2006). This may explain the discrepancies between our results and those of de Blois et al (2001).…”
Section: Spatial Variablescontrasting
confidence: 60%
“…Several works have shown that land-use history can have long-term effects on woody species composition (de Blois et al 2001;Bellemare et al 2002;Onaindia et al 2004). In our study area, previous works (Guyon et al 1996;De Warnaffe et al 2006) have shown a lengthening of cutting regimes which could also explain the distribution of the tree species in the upper and understory layers according to their shade tolerance.…”
Section: Environmental Conditionsmentioning
confidence: 92%
See 2 more Smart Citations
“…Indeed, increased light intensity is commonly found at open edges, a feature that is reversed as edges mature (Ranney et al, 1981). Our results are consistent with this statement, as we suspect that our edges are "open edges", as they are more frequently logged than woodlot interiors (De Warnaffe et al, 2006). Birddispersed species had higher seedling abundances at forest edges, consistently with previous work reporting higher densities of bird-dispersed species at edges (Ranney et al 1981).…”
Section: Spatial Pattern According To the Distance From The Forest Edgesupporting
confidence: 82%